Productive and qualitative performance of tomato plants as a function of the application of plant growth regulators and mineral nutrients - Caixeta Sousa, Marília; Rodrigues, Luan Fernando Ormond Sobreira; Silva, Mônica Bartira da; Cruz, Janaina Oliveira; Diamante, Marla Silvia; Martins, Bruno Novaes Menezes; Simonetti, Lilian Massaro; Rodrigues, João Domingos (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The tomato fruit is rich in antioxidant compounds and has great nutritional and economic importance, annually promoting research on the nutritional and productive characteristics. The present study aimed to evaluate whether foliar application of commercial products based on growth regulators [auxin, cytokinin and gibberellin (Ax+CK+GA)], micronutrients [cobalt and molybdenum (Mi)] and mixtures of macro and micronutrients [nitrogen, boron, copper, molybdenum and zinc (Ma+Mi)], isolated and in combination, increase productivity and improve the post-harvest quality of tomato fruits (Predador F1). The experiment design used randomized blocks, with seven treatments and four repetitions, which were (T1) control; (T2) Ax+CK+GA; (T3) Ma+Mi; (T4) Mi; (T5) Ax+CK+GA + (Ma+Mi); (T6) Ax+CK+GA + Mi; and (T7) Ax+CK+GA + Mi + (Ma+Mi). The variables production, precocity, soluble solids content (SS), titratable acidity (TA), ratio (SS/TA), pH, total soluble sugars, ascorbic acid and weight loss were evaluated. The Ax+CK+GA application, isolated or in combination with Ma+Mi, promoted the precocity, and the use of isolated Ax+CK+GA and Mi improved the tomato plant productivity. The growth regulators, macro and micronutrients, isolated or in combination, increased the ascorbic acid content in the fruits.